2003
DOI: 10.1177/001698620304700306
|View full text |Cite
|
Sign up to set email alerts
|

Early-Entrance Students: Impressions of Their First Semester of College

Abstract: Although the long-term impact of early entrance to college has been examined, one issue that has received inadequate attention in the gifted education literature is how students enrolled in early-entrance programs adjust during their first semester of college, which is arguably the most critical juncture for them in terms of their transition from high school. The purpose of this study was to identify the unique academic, social, family, and transition issues that challenged the inaugural class of the National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 18 publications
(27 reference statements)
5
43
0
Order By: Relevance
“…Similarities were also found in the establishment of satisfying friendships with older students, the possession of a wide range of interests, and involvement in cocurricular activities. The generally positive academic and socioemotional outcomes for the radical accelerands are consistent with studies undertaken outside of Australia that have suggested that early college entrants tend to demonstrate academic successes and (usually) positive socioemotional adjustment (Boazman & Sayler, 2011;Brody et al, 2004;Muratori et al, 2003;Robinson, 2004;Shepard, Foley Nicpon, & Doobay, 2009).…”
Section: Summary Of Researchsupporting
confidence: 78%
See 3 more Smart Citations
“…Similarities were also found in the establishment of satisfying friendships with older students, the possession of a wide range of interests, and involvement in cocurricular activities. The generally positive academic and socioemotional outcomes for the radical accelerands are consistent with studies undertaken outside of Australia that have suggested that early college entrants tend to demonstrate academic successes and (usually) positive socioemotional adjustment (Boazman & Sayler, 2011;Brody et al, 2004;Muratori et al, 2003;Robinson, 2004;Shepard, Foley Nicpon, & Doobay, 2009).…”
Section: Summary Of Researchsupporting
confidence: 78%
“…Young (2010) undertook 12 case studies of early college entrants, of which two were admitted without the completion of secondary school, one experienced dual enrollment, and nine were accelerated by 1 or more years in elementary and/or secondary school. Similar to the findings of studies undertaken outside of Australia (e.g., Muratori, Colangelo, & Assouline, 2003), many of the participants had negative experiences prior to entering college, with five unable to find a social niche, a number of instances of bullying, multiple examples of intellectual frustration and boredom, and feelings of being "out of place." Nevertheless, some of the participants were able to find peers in academically selective secondary schools, through their involvement in extracurricular activities, or with other "social outcasts."…”
Section: Summary Of Researchsupporting
confidence: 69%
See 2 more Smart Citations
“…Yet schools and educators generally use acceleration very conservatively or not at all (Colangelo, Assouline, & Gross, 2004), particularly with gifted low-income or minority students who are underrepresented in many gifted programs (Bernal, 2002;Ford, Harris, Tyson, & Trotman, 2002;Grantham, 2003;Lee, Matthews, & Olszewski-Kubilius, 2008;Morris, 2002;Worrell, 2007;Wyner, Bridgeland, & Diiulio, 2007). Almost none of the research on acceleration to date has been conducted with low-income or minority students exclusively or with samples containing large numbers of these students in contrast to substantial studies on acceleration involving nonminority students (Colangelo et al, 2004;Gross, 2003;Janos & Robinson, 1985;Muratori, Colangelo, & Assouline, 2003;Rogers, 1991Rogers, , 2002Rogers & Span, 1993;Sayler & Lupkowski, 1992;Swiatek, 1993Swiatek, , 2002.…”
Section: Introductionmentioning
confidence: 99%